Genetic engineering of apple (Malus domestica Borkh.) for resistance to fungal diseases using g2ps1 gene from Gerbera hybrida (Asteraceae) - Ali Bacha, N. M.; Batha, M.; Abdul-Kader, A. M. (International Journal of Horticultural Science, 2014)
In the present study, g2ps1 gene from Gerbera hybrida coding for 2-pyrone synthase which contribute for fungal and insect resistance was used. The aim was to work out an efficient approach of genetic transformation for apple cvs. ‘Golden Delicious’, ‘Royal Gala’ and ‘MM111’, ‘M26’ rootstocks for improving their fungal resistance using genetic engineering techniques. Adventitious shoot formation from leaf pieces of apples studied was achieved using middle leaf segments taken from the youngest leaves from in vitro-grown plants.Optimum conditions for ‚direct’ shoot organogenesis resulted in high regeneration efficiency of  0%, 95%, 92%, 94% in the studied apples respectively. Putative transgenic shoots could be obtained on MS media with B5 Vitamins, 5.0 mg l-1 BAP, or 2.0 mg l-1 TDZ with 0.2 mg l-1 NAA in the presence of the selection agent “PPT” at 3.0-5.0 mgl-1. Shoot multiplication of transgenic shoots was achieved on: MS + B5 vitamins + 1.0 mg l-1 BAP + 0.3 mg l-1 IBA, 0.2 mg l-1 GA3+1.0 g/l MES+ 30 g/l sucrose + 7.0 g/l Agar, with the selection agent PPT at 5.0 mg l-1 and were subcultured every 4 weeks in order to get sufficient material to confirm transformation of the putative shoots obtained. Six, seven, one and six transgenic clones of the apples studied respectively have been obtained and confirmed by selection on the media containing the selection agent “PPT” and by PCR analysis using the suitable primers in all clones obtained for the presence of the selection” bar gene (447 bp) and the gene-of- interest “g2PS1” (1244 bp), with transformation efficiency of 0.4%, 0.6%, 0.1% and 0.3% respectively. These transgenic clones were multiplied further in vitro in the presence of the selection agent ‘PPT’ and rooted in vitro. Rooted transgenic plantlets were successfully acclimatized and are being kept under-containment conditions according to the biosafety by-law in Syria to evaluate their performance for fungal resistance .